Menyusun Rencana Strategis untuk Ketersediaan Guru dan Tenaga Kependidikan: Tinjauan Analitis dan Solusi Prospektif - Fauziah, Elly Ayu; Aini, Nurul; Nurhidayah, Paramita; Khikmah, Alifatul (TSAQOFAH, 2024)
Human resource planning in education plays an important role in improving the quality of education. This research aims to reveal the results of research regarding the analysis of planning needs for teachers and education personnel at SDN Lidah Kulon IV, Surabaya. This research method uses a qualitative approach and descriptive research type. Data collection techniques were observational and interviews with school principals. The research results showed that the school collaborated with the Surabaya City Education Office in HR planning. However, schools do not have independent authority in teacher placement. The main challenge faced is a shortage of teachers which has resulted in double workloads for some teachers. To overcome this, SDN Lidah Kulon IV utilizes IT personnel to teach. However, the position of IT personnel has not been officially recognized as a teacher. In conclusion, educational human resource planning requires good coordination between schools and related agencies to ensure teacher needs are met effectively and efficiently.